Efektivitas Model PBL-STEM Berbantuan Google Sites Terintegrasi Video Pembelajaran terhadap Literasi Matematika - Rekyan Ananta Vera; Arief Agoestanto (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
One of the essential skills in the 21st century is mathematical literacy. However, the average level of mathematical literacy in Indonesia remains low. This study aims to examine the effectiveness of the PBL-STEM model supported by Google Sites integrated with instructional videos on mathematical literacy. This research employs a quantitative approach. Data collection was conducted through tests, which were then analyzed using t-test, z-test, and N-Gain test. The PBL-STEM model supported by Google Sites integrated with instructional videos has proven to be effective in improving mathematical literacy. The results indicate that students’ mathematical literacy using this model achieved a BTA above 70%, with higher averages and completeness proportions compared to the PBL model. The average posttest score reached 86.67, higher than the pretest score of 63.3, and the N-Gain average of 0.49 indicates a moderate improvement.